Perceived social undermining keeps entrepreneurs up at night and disengaged the next day: The mediating role of sleep quality and the buffering role of trait resilience - Yu, Wei; Li, Zhuyi Angelina; Foo, Maw-Der; Sun, Shuhua (Journal of Business Venturing, 2022)
Entrepreneurs work in an uncertain, novel, and high-stakes environment. This environment can lead to disagreements and conflicts over how to develop, grow, and run a business venture, thus triggering destructive social interactions. This research sheds light on the role of destructive interpersonal relationships by examining daily perceived social undermining from work partners and how and when this perceived undermining affects entrepreneurs' work engagement. Building on a resource-based self-regulation perspective, we develop a theoretical model of the self-regulation impairment process whereby an entrepreneur's perceived social undermining disrupts sleep quality at night, which dampens work engagement the next day. We further theorize trait resilience as a self-regulation capacity that buffers this impairment process. We test the model in a study based on daily surveys over 10 workdays from 77 entrepreneurs. The results largely support our hypotheses and further indicate that trait resilience is more crucial for less experienced entrepreneurs. Our study contributes to research on how entrepreneurs' interpersonal relationships—particularly destructive ones—affect entrepreneurial well-being.